The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.foodhyd.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Surface structural features control in vitro digestion kinetics of bean starches

Abstract: Although many studies have investigated the enzyme susceptibility of bean starches, the factors that reduce the lower hydrolysis of bean starch are not well understood. In the present study, we isolated starches from eight commercial bean varieties and established a causal relationship between micro and macro-structure with α-amylase susceptibility. The in vitro starch digestion kinetic profiles were monitored at a fixed enzyme concentration, and the data were fitted into the Logarithm of Slope model to obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 43 publications
1
14
1
1
Order By: Relevance
“…The controlled thermal treatment of starch lead to the decrease in the structural orders and increase in the digestion extent of the starch. These findings were found contrary to the results of Li et al (2017) [14], where no correlation was observed between the structural parameters of native bean starches and their digestibility. A strong positive correlation was observed in the viscosity (P.V.…”
Section: Pearson's Correlation Analysiscontrasting
confidence: 99%
See 2 more Smart Citations
“…The controlled thermal treatment of starch lead to the decrease in the structural orders and increase in the digestion extent of the starch. These findings were found contrary to the results of Li et al (2017) [14], where no correlation was observed between the structural parameters of native bean starches and their digestibility. A strong positive correlation was observed in the viscosity (P.V.…”
Section: Pearson's Correlation Analysiscontrasting
confidence: 99%
“…The accountable reason was said to be the damaged starch granules and the internal crack of hilum. However, Li et al listed disruption of double-helical structure and crystallinity to be the determinants in the digestion of starches which is in accordance with our findings from FTIR and XRD as they also indicated the disruption in double helical structure and crystallinity [14]. The relation between starch structure and digestion is complex which depends on various factors such as amylose content, orientation of amylopectin, degree of crystallization and the particle size [42].…”
Section: In Vitro Digestion Kineticssupporting
confidence: 87%
See 1 more Smart Citation
“…O amido é a principal substância de reserva das leguminosas, e está presente em vários tipos de tecidos e órgãos nas plantas, como folhas, raízes, brotos, frutos, grãos e caules, como fonte de reserva energética (STEADMAN et al, 1996;AVÉROUS;HALLEY, 2014). A composição química do amido compreende cadeias predominantemente lineares de amilose e cadeias ramificadas de amilopectina, densamente empacotadas em uma estrutura granular semicristalina (LI et al, 2018). A grande maioria dos amidos contém de 20 a 30% de amilose e 70 a 80% de amilopectina e essa razão se altera conforme a fonte botânica (CORDENUNSI et al, 2006).…”
Section: Composição Química De Sementesunclassified
“…However, faba bean use in broiler diet is limited due to a lower protein content compared to soybean meal (SBM) and to the presence of several anti-nutrients (Jezierny et al 2010). In addition, as the type of crystal structure present in starch granules may influence its digestibility (Ao et al 2007;Zhang et al 2006), in vitro studies (Hoover and Zhou 2003;Li et al 2018;Weurding 2002) showed that type-C starch from legumes is more slowly and to a lesser extent digested than type-A starch from cereals (Sun et al 2006). Similarly, studies with broiler chickens showed that legume starch is generally more resistant to intestinal degradation than cereal starch (Carre et al 1991;Carré et al 1998;Wiseman 2006).…”
Section: Introductionmentioning
confidence: 99%